UVR-B-induced NKR-1 Expression in Ocular Tissues is blocked by Substance P Receptor Antagonist Fosaprepitant in the Exposed as well as Unexposed Partner Eye. (4th July 2021) - Gross, Janine; Wegener, Alfred R.; Kronschläger, Martin; Schönfeld, Carl-Ludwig; Holz, Frank G.; Meyer, Linda M.
ABSTRACT: Purpose : To investigate the effect of NKR-1 antagonists in an established UVR-B-induced cataract mouse model. Furthermore, to examine the expression of pro-inflammatory cytokines/chemokines in mouse eyes following unilateral UVR-B exposure. Methods : Mice received intraperitoneally injections of Fosaprepitant and Spantide I, before and after unilateral exposure to UVR-B. After day 3 and 7 post-exposure, ocular tissues were extracted for the detection of NKR-1 protein level by ELISA. Results : Pretreatment with Fosaprepitant decreases NKR-1 expression in exposed ocular tissues as well as in the unexposed lens epithelium compared to the saline group. Spantide I treatment showed a tendency of NKR-1 overexpression in ocular tissues. Conclusion : The clinically approved NKR-1 receptor antagonist Fosaprepitant decreases NKR-1 protein expression effectively not only in the exposed but also in the unexposed partner eye in a UVR-B irradiation mouse model. No effect was seen on the protein concentration of pro-inflammatory cytokines/chemokines in either eye.